FORMATION OF A RELATIONSHIP OF RESPONSIBILITY TO THE FAMILY IN YOUNG PEOPLE - Yuldoshev Tojiddin Abdukarimovich; Urozov Fakhriddin Isokovich; Shomurotov Ulug’bek Melikmurodovich (European Journal of Humanities and Educational Advancements, 2023)
Family Relations, their educational and educational capabilities, family spiritual and moral values and problems of their formation. This is explained both by the importance of the problem itself, which may depend on the number of" eternal " subjects, and by the intensive processes associated with the institution of the family at the present stage of the development of society. This creates a number of complex problems and contradictions. In this article, opinions and considerations are made about the formation of responsible relationships to the family in young people.